ИЛИМ ТАРИЙХЫНДА ИЛИМЛЕРДИ КЛАССИФИКАЦИЯЛАЎ МАШҚАЛАСЫ - Есназарова, З.Б.; Хужаниязов, У.Е. (FAN va JAMIYAT, 2025)
The article focuses on the problem of classifying science. At the same time, the classification of scientific knowledge that arose in classical philosophy from Aristotle to our day is mainly considered. The issues of classification of sciences by hierarchical and historical foundations, the role of social and human sciences in the system of scientific knowledge are illuminated.